Global Bifurcation of Fourth-Order Nonlinear Eigenvalue Problems’ Solution - Fatma Aydin Akgun (International Journal of Differential Equations)
In this paper, we study the global bifurcation of infinity of a class of nonlinear eigenvalue problems for fourth-order ordinary differential equations with nondifferentiable nonlinearity. We prove the existence of two families of unbounded continuance of solutions bifurcating at infinity and corresponding to the usual nodal properties near bifurcation intervals.